2011
DOI: 10.1111/j.1477-2574.2010.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth factor levels after thermal ablation in a murine model of colorectal liver metastases

Abstract: Tumour induces upregulation of TGF-β and VEGF in liver parenchyma. Growth factors decreased after TA, but this appears to be the result of the experimental procedure rather than the TA itself. However, TA resulted in increased levels of TGF-β, which may contribute to tumour recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In this study we observed significant upregulation of c-Met and EGFR in liver tissues early Further studies are required to assess this hypothesis in our settings. Interestingly, our group has previously shown that the induction of colorectal liver metastases in this mouse model causes upregulation of TGF-and VEGF in the liver parenchyma by day 21, compared with normal liver (liver with no tumours) [54]. These findings further support the hypothesis of a cross-talk between tumour and stromal cells, both within the tumour and the adjacent liver.…”
Section: Liver Regeneration and Tumour Inductionsupporting
confidence: 75%
“…In this study we observed significant upregulation of c-Met and EGFR in liver tissues early Further studies are required to assess this hypothesis in our settings. Interestingly, our group has previously shown that the induction of colorectal liver metastases in this mouse model causes upregulation of TGF-and VEGF in the liver parenchyma by day 21, compared with normal liver (liver with no tumours) [54]. These findings further support the hypothesis of a cross-talk between tumour and stromal cells, both within the tumour and the adjacent liver.…”
Section: Liver Regeneration and Tumour Inductionsupporting
confidence: 75%
“…In a previous study, thermal ablation of murine colorectal liver metastases (CRCLM) was shown to induce the upregulation of HSPA1A in residual tumour cells that peaked at 24 h post-treatment (Nikfarjam et al 2005). In the present study, we used archival tissues from a previous investigation (Fifis et al 2011) to determine whether thermal ablation stimulated an EMT in the residual tumour fraction. Immunohistochemical analysis demonstrated that untreated tumours expressed high levels of E-cadherin ( Fig.…”
Section: Thermal Ablation Treatment Induces Emt In Residual Tumour Frmentioning
confidence: 94%
“…For example, epidermal growth factor receptor activation has been linked to early failure of c-Met inhibition in the treatment of lung cancer (41). Other growth factors and cytokines that have been identified as drivers of tumor growth (including hypoxia-inducible factor-1a and interleukin-6) are also upregulated after RF ablation (4,42). Several of these are linked with c-Met activation through shared downstream mediators or direct involvement in the c-Met pathway (43).…”
Section: Experimental Studies: Suppression Of Radiofrequency Ablationmentioning
confidence: 99%